Synthesis, photophysical properties and DFT studies of 2-(3-cyano-4-((2-(4,6-dimethyl-5-nitro-1H-pyrazolo[3,4-b]pyridin-3-yl)hydrazono)methyl)-5,5-dimethylfuran-2(5H)-ylidene)malononitrile dye - Hana M. Abumelha; Abrar Bayazeed; Omaymah Alaysuy; Amerah Alsoliemy; Arwa Alharbi; Turki M. Habeebullah; Nashwa M. El-Metwaly (Journal of Saudi Chemical Society, 2022)
The chromophore 2-(3-cyano-4-((2-(4,6-dimethyl-5-nitro-1H-pyrazolo[3,4-b]pyridin-3-yl) hydrazono)methyl)-5,5-dimethylfuran-2(5H)-ylidene)malononitrile (PPHTCF) was synthesized through coupling of diazotized 3-amino-4,6-dimethyl-5-nitropyrazolo[3,4-b]pyridine with 3-cyano-2-(dicyanomethylene)-4,5,5-trimethylfuran (TCF). The absorption solvatochromism behaviour of PPHTCF, in various solvents, presented ΔEmax = +5.40 where the positive sign suggested red shift occurrence, implying that the PPHTCF has more polar lowest excited state than its ground one. While, the PPHTCF fluorescence spectra afforded λem, in 575–633 nm range, and was more dependent on the solvent polarity than the absorption λmax, despite both exhibited red shift by 58 and 42 nm, respectively. To discover the PPHTCF solvatochromism behaviour in term of “Stokes’ shift”, both of Lippert-Mataga and linear solvation-energy relationship (LSER) formulations have been utilized and the outcomes endorsed that the later was better than the former (R2 = 0.9728). Finally, TD-DFT simulated absorption and emission spectra in EtOH revealed that λmax has been resulted mainly from HOMO → LUMO; HOMO-5 → LUMO and HOMO-2 → LUMO transitions, respectively.